2001
DOI: 10.2175/106143001x138688
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Drinking Water Treatment Residuals for Use as a Soil Substitute

Abstract: The beneficial use of drinking water treatment residuals (WTRs) as a potential source of topsoil for land reclamation was evaluated. Seventeen WTRs were characterized for use as soil substitutes by comparing chemical and physical properties and plant nutrients of the WTRs with soil. A tomato (Lycopersicon esculentum) bioassay was performed to determine the ability of soil chemical tests to measure WTR phosphorus (P) adequacy. The WTR chemical and physical properties were typically adequate for crop growth. Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
61
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 17 publications
12
61
0
6
Order By: Relevance
“…Dayton and Basta (2001) further provided evidence using the toxicity characteristic leaching procedure (TCLP) on selected waterworks residual, that the heavy metal levels in the sludge residues were significantly less than the regulatory levels for TCLP and consistent with nonhazardous waste metals. This is in agreement with the result of a similar study on the average level of metals found in waterworks sludge (Elliot and Dempsey, 1991).…”
Section: Toxicitymentioning
confidence: 98%
See 1 more Smart Citation
“…Dayton and Basta (2001) further provided evidence using the toxicity characteristic leaching procedure (TCLP) on selected waterworks residual, that the heavy metal levels in the sludge residues were significantly less than the regulatory levels for TCLP and consistent with nonhazardous waste metals. This is in agreement with the result of a similar study on the average level of metals found in waterworks sludge (Elliot and Dempsey, 1991).…”
Section: Toxicitymentioning
confidence: 98%
“…Dayton and Basta (2001) noted that waterworks sludge might be suitable for use as soil substitutes since they predominantly contain humic substances and sediments from the raw water, which makes them similar to fine textured soils. A classification analyses based on British standards BS 3882 revealed that water treatment works sludges could be classified as "economy grade-high clay content" soil indicating their possible use as soil or in soil making materials (Owen, 2002).Such approaches may provide an economical disposal means for the sludge while probably serving to improve certain soil qualities and enhance plant growth.…”
Section: For Structural Soil Improvementmentioning
confidence: 99%
“…A viabilidade desta aplicação é determinada pelas características físicas e químicas dos lodos, notadamente pela existência de nutrientes benéficos às culturas e pela ausência de contaminantes (Dayton et al, 2001).…”
Section: Uso De Lodos Em Solosunclassified
“…Existem vários trabalhos na literatura nacional e internacional sobre o tema, tais como disposição em ETEs (Carvalho, 2000;Scalize, 2003;Ferreira Filho e Waelkens, 2009;Scalize e Di Bernardo, 2011;Di Bernardo et al, 2011), fabricação de materiais cerâmicos (Oliveira e Holanda, 2008;Tartari et al, 2011) e de tijolos (Teixeira et al, 2006), recuperação de áreas degradadas (Teixeira et al, 2005(Teixeira et al, e 2007Moreira et al, 2009), aplicações agrícolas (Dayton and Basta, 2001;Botero et at, 2009;Park et al, 2009;OH et al, 2010;Figueiredo Neto et al, 2012) e minimização de RETA (Achon et al, 2008;Ferreira Filho e Waelkens, 2009).…”
Section: Introductionunclassified